Trauma-informed pedagogy : addressing gender-based violence in the classroom - Marshall, Jocelyn E.; Skibba, Candace (Emerald Publishing Limited, 2022)
Gender-based violence is an issue often met with silence, unempathetic discourse, and troublesome visual representation. As educators, mentors, and public facilitators, how can we address this subject in our teaching spaces, curricula, texts, and conversations with greater care and understanding? And, what do we need as resources to cultivate these deeper insights and new roads to increased awareness and dynamic healing? Building decentered and empowering spaces is vital to addressing gender-based violence. In an educational setting, this must take into consideration instructors', students', and other professionals' own histories of and relationships to traumatic experience. The authors provide a cross-disciplinary dialogue involving spaces ranging from first-year writing programs to international classrooms to public art installation. What holds the conversation together is a collective emphasis on transnational feminist pedagogy and pedagogy of the oppressed while also prioritizing affective discourse. This combination of approaches is used to not only open the conversation itself, but to also pointedly deconstruct standard patriarchal practices found in academia and other institutional settings. With contributions from scholars and practitioners from a variety of disciplines, cultures and educational backgrounds, Trauma-Informed Pedagogy brings visibility to perpetuated violence and silence through a range of genres, including poetry, syllabi, and critical reflections, offering an invaluable resource for instructors and workshop facilitators interested in approaches that decentralize learning spaces and empowers all participants.